Identification of Escherichia coli in Gado-Gado Sold Around Tadulako University - Nur Amal; I Nengah Kundera; Syech Zainal; Yulia Windarsih; Rafiqa Rafiqa; Abdul Ashari (Biology, Medicine, & Natural Product Chemistry, 2026)
Escherichia coli is a pathogenic bacterium that has the potential to contaminate food. Certain strains of E. coli exhibit pathogenic properties and may cause infections in hosts. The presence of pathogenic bacteria in food is a critical concern in food safety. This study aimed to identify the presence of E. coli in gado-gado sold in the canteens of Tadulako University. This research employed a descriptive exploratory laboratory approach. Samples were collected from five different canteens using random sampling techniques. Microbiological analyses were conducted using the Most Probable Number (MPN) method, Total Plate Count (TPC), Gram staining, cultivation on selective Eosin Methylene Blue Agar, and biochemical testing using Triple Sugar Iron Agar. The results showed that the average Most Probable Number was 4,900 MPN /mL of sample, while the Total Plate Count averaged 35,800 CFU/mL. This TPC value exceeds the standard set by the Indonesian Food and Drug Authority (BPOM) of 104 CFU/g, indicating that the food products do not meet the required health standards. Confirmatory tests on Eosin Methylene Blue Agar showed colony growth with a metallic green sheen and reddish coloration, characteristic of Gram-negative bacilli. Biochemical testing on Triple Sugar Iron Agar yielded positive results consistent with the biochemical characteristics of E. coli. Therefore, the findings confirm the presence of E. coli in the analyzed samples.